(untitled) (Journal of Civil Engineering Researchers, 2026)
This paper studies the structural behavior of prestressed concrete beams and steel fiber reinforced concrete piles. A nonlinear finite element formulation based on the principle of virtual work is developed to analyze the response of these prestressed structural elements under applied loads. The model accounts for material nonlinearity, second-order effects, and variable stiffness through an incremental loading procedure. Simpson’s integration scheme is adopted to evaluate the cross-sectional response of each element. The governing equations describing beam behavior are established, and the influence of compressive strength and prestressing force on structural performance is examined. Experimental tests conducted on prestressed concrete beams and steel fiber–reinforced concrete piles are used to validate the proposed approach. A comparison between numerical and experimental results demonstrates the accuracy and reliability of the developed formulation.